2015
DOI: 10.1002/wat2.1079
|View full text |Cite
|
Sign up to set email alerts
|

Increasing river floods: fiction or reality?

Abstract: There has been a surprisingly large number of major floods in the last years around the world, which suggests that floods may have increased and will continue to increase in the next decades. However, the realism of such changes is still hotly discussed in the literature. This overview article examines whether floods have changed in the past and explores the driving processes of such changes in the atmosphere, the catchments and the river system based on examples from Europe. Methods are reviewed for assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
121
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 62 publications
3
121
0
1
Order By: Relevance
“…The hypothesis that frequencies of river floods in Europe may increase in the future due to climate change is widely discussed among scientists (Hall et al, 2014;Blöschl et al, 2015). Lehner et al (2006) as well as Dankers and Feyen (2008), for example, concluded that the frequency (and magnitude) of flooding in large parts of Europe is projected to increase in future, i.e.…”
Section: Flood Risk and Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis that frequencies of river floods in Europe may increase in the future due to climate change is widely discussed among scientists (Hall et al, 2014;Blöschl et al, 2015). Lehner et al (2006) as well as Dankers and Feyen (2008), for example, concluded that the frequency (and magnitude) of flooding in large parts of Europe is projected to increase in future, i.e.…”
Section: Flood Risk and Climate Changementioning
confidence: 99%
“…Furthermore, future trends of climatic extremes cannot be projected with sufficient reliability, in particular with respect to heavy rainfall, which considerably contributes to raingenerated local flooding in most cases (Hanel and Buishand, 2010;IPCC, 2012). Blöschl et al (2011) presented a study addressing the issue of changing flood frequencies in Austria due to climate change. According to them, the above-mentioned complexities and uncertainties also apply on the national level, which makes a reliable projection of future trends nearly impossible against current knowledge.…”
Section: Flood Risk and Climate Changementioning
confidence: 99%
“…To explain the lack of correlation in the Sierra de Guadarrama mountain range, we believe that the capacity of a catchment to deliver unconsolidated material during events -which is in addition capable of damaging existing trees -is the key, but this element never appears explicitly among the geomorphic parameters used in our discipline. Blöschl et al (2015), Borga et al (2014) and Marchi et al (2009), for instance, emphasized that soil characteristics, such as hydraulic conditions, saturation and infiltration, play an important role in the activation of rapid runoff which can eventually become prevailing transfer processes. The upper part of the PU catchment, where large flash flood activity has been observed, is in fact characterized by extensive deposits of unconsolidated material (i.e., fine-grained rock and soil debris from periglacial activity) occupying steep slopes void of vegetation (Fig.…”
Section: Tablementioning
confidence: 99%
“…Such conditions will, in fact, favor subsuperficial runoff, especially in combination with snowmelt processes, thereby also increasing the possibility for debris to be mobilized (Costa, 1984). Specifically, Blöschl et al (2015), remark that the occurrence of river floods triggered by rainfall and snowmelt are also related with processes occurring at atmospheric and river system (i.e. flood wave propagation and superposition of flood waves) levels.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation